Determinan Kinerja Pegawai dengan Self Control sebagai Variabel Moderating - Putri, Trisna Eka; Ramadhani, Sri (SAFE-Network, 2023)
This study aims to empirically prove the influence of Work Motivation, Work Stress and Cyberloafing on Employee Performance with Self Control as a moderating variable. The population in this study were employees of the Medan MSME Cooperative Service Office. The independent variables used are employee motivation, work stress and cyberloafing, 1 dependent variable is employee performance and 1 moderating variable is self control. The number of samples used in this study amounted to 40 people using the Simple Random Sampling method. The data analysis technique used is multiple linear regression, moderation regression test and hypothesis test. The results showed that work motivation, work stress and cyberloafing have a significant effect on employee performance partially and simultaneously. Meanwhile, Self Control is able to moderate the influence of work motivation, work stress and cyberloafing which have a significant effect on employee performance.